2011
DOI: 10.1890/es10-00183.1
|View full text |Cite
|
Sign up to set email alerts
|

Reintroducing fire into a ponderosa pine forest with and without cattle grazing: understory vegetation response

Abstract: Abstract. Reestablishing historical fire regimes is a high priority for North American coniferous forests, particularly ponderosa pine (Pinus ponderosa) ecosystems. These forests are also used extensively for cattle (Bos spp.) grazing. Prescribed fires are being applied on or planned for millions of hectares of these forests to reduce fuel loads, alter forest structure, and maintain and enhance the productivity of native plant communities. However, cattle grazing is ubiquitous in ponderosa pine forests and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
(59 reference statements)
5
21
1
Order By: Relevance
“…For example, unsatisfactory gains in cover and richness on more mesic sites might indicate further overstory manipulations are required to create openings and reach a basal area of $6 m 2 ha À1 , a threshold below which understory communities have been shown to respond (Sabo et al, 2008). Additionally this might suggest testing seeding as an additional treatment, or help managers decide whether grazing should be reduced or deferred for a period of time (Kerns et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For example, unsatisfactory gains in cover and richness on more mesic sites might indicate further overstory manipulations are required to create openings and reach a basal area of $6 m 2 ha À1 , a threshold below which understory communities have been shown to respond (Sabo et al, 2008). Additionally this might suggest testing seeding as an additional treatment, or help managers decide whether grazing should be reduced or deferred for a period of time (Kerns et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen mineralization rates may also be affected by higher soil moisture and temperature, which occurred on the fall burn treatments but not the spring burn treatments. There are at least two N fixing species at this site: L. caudatus and C. velutinus (Kerns et al, 2011). L. caudatus is a perennial forb which as a class accounted for less than 7% of the cover across all treatments (no significant differences among control, fall-5, or spring-5 treatments).…”
Section: Available Nutrientsmentioning
confidence: 91%
“…These initial burns had the highest severity compared to the second burn likely due to high fuel loading. As a result of the second fire, fuels were reduced 23-25% with significant reductions in the O horizon, 10-h, and 100-h fuels (Kerns et al, 2011). Both fall and spring prescribed burning had an effect on fuels on these sites.…”
Section: Available Nutrientsmentioning
confidence: 98%
“…Ponderosa pine trees in the study area are approximately 80-100 years old with infrequent individuals of about 200 years old (Emigrant Creek Ranger District, unpublished data). Understory species composition varies among the sites (Kerns et al 2006(Kerns et al , 2011, but P. ponderosa/Pseudoroegneria spicatum (Pursh) Á. Löve and P. ponderosa/ Carex geyeri Boott are the major plant associations. Each stand was thinned in 1994 or 1995.…”
Section: Study Areamentioning
confidence: 99%
“…Each stand was thinned in 1994 or 1995. More extensive details on the study area and the experiment can be found in Thies et al (2005Thies et al ( , 2006; and Kerns et al (2006Kerns et al ( , 2011.…”
Section: Study Areamentioning
confidence: 99%